Bruce Bronzan Campaign Retreat at Morris Cabin-Shaver Lake - Watkins, Howard::::::::: (1978)
Christine Watkins, David Brodie, Randy Walsh, Sandy Walsh, ?, Bruce Bronzan, Doug Broten, Raul Martinez Timeline chart on floor